Microbiome drives age-dependent shifts in brain transcriptomic programs at the single-cell level in Drosophila - Dianshu Zhao; Russel T. Shiga; Zhangrong Song; Runhang Shu; Lipin Loo; Adam Chun Nin Wong (npj Biofilms and Microbiomes)
Abstract The gut microbiome plays a critical role in brain function and the brain-gut axis, yet its cellular and molecular mechanisms remain unclear. Here, we present the first comprehensive single-cell transcriptomic atlas of brain cells from adult Drosophila melanogaster raised under axenic and microbiome-associated conditions, spanning young and old ages. Profiling 34,427 cells across 101 clusters, we annotated 56 cell types and identified cell type-specific gene signatures influenced by the microbiome. Transcriptional shifts were most pronounced in old flies, with glial cells and dopaminergic neurons among the most microbiome-responsive cell types. Differentially expressed genes (DEGs) were enriched in pathways related to mitochondrial activity, energy metabolism, and Notch signaling. We also quantified age-associated changes in the gut microbiome, observing reduced Acetobacter dominance and increased microbial diversity that corresponded with heightened brain transcriptional responses. These findings illuminate the cell type-specific impacts of the microbiome on brain gene expression and lay the groundwork for understanding the molecular underpinnings of the microbiome-gut-brain axis.